Design of interactive multimedia courseware in data structures & algorithms I - Lim, Jia Xuan. (2013)
This report accounts the author’s experience in completing her Final Year Project (FYP) on developing an interactive multimedia courseware in Data Structure and Algorithms, specifically on the topic of Pseudocode. This report begins with the basic introduction of the project and the overview of the methodology to develop a courseware. It shares the process of the project that the author has done using the various programming tools and language such as; Adobe Flash, XML file, ActionScript, PHP and MySQL Database. In addition, this project also achieves to allow the user to access the courseware through internet. Lastly, this report sums up the valuable experience and lessons the author has achieved during this period, and thus concluding her FYP.